Double or nothing: Push and pull factors of casinos in Europe - Carvalho, N.; Rodrigues, H.; Brochado, A. (GeoJournal, 2023)
Gambling tourism is a subject that has been gaining a lot of interest and notoriety over the last two decades. Push and pull factors have for long been the backbone of tourism studies and this research seeks to expound on this theory within the area of casinos. In this study, 1383 google reviews from five different countries in coastal Europe: Casino Vila Moura, Algarve (Portugal), Casino Barrière Le Croisette, Cannes (France), Casino de Monte-Carlo, (Monaco), Casino Malta, (Malta), and Regency Casino Thessaloniki, (Greece) were analyzed with the software Leximancer. The main objective of this study was to identify the concepts in the reviews and then pinpoint what push and pull factor these concepts belonged to and how important this was when choosing a casino destination in Europe. The results highlight the importance of the pull factor while choosing a destination and reveals that gamers seek mainly table games as they attract both players and other tourists who tend to gather around the tables to watch. Among the greatest push-factors is the excitement of winning money in slot machines. Findings also demonstrate that casinos located in Europe offer world-class gambling services that are both engaging and fun to engage in. This study adds to earlier research by employing the push and pull motivation framework within the area of casinos based on user-generated content.